Karakteristik Graf Pembagi Nol Pada Gelanggang Bilangan Bulat Modulo - Rina Juliana (Universitas Nusa Cendana, 2022)
Zero-divisor graph is a geometric representation of a commutative ring. Zero-divisor graph of ring R that denoted by TR, defined by a graph whose vertices are all elements of zero-divisor set of a ring R, and two distinct vertices a and b are adjacent if and only if ab=0. In this paper, we will study some of the characterizations of the zero-divisor graph of integers modulo ring ( Zn). This study aims to know some forms of zero-divisor graph of ring (Zn ) and its properties. The method that used in this paper is deductive proof, by taking some example of zero-divisor graph of integer modulo ring ( Zn), then generalized the characterization of example. The firts result is if n=p^2, with p is a odd prime number, then the zero-divisor graph of ring is a complete graph. Then the second result is if n=p1p2, with p1 and p2 are different prime numbers, then the zero-divisor graph of ring is a complete bipartite graph and the diameter is 2.